2006
DOI: 10.1074/jbc.m601820200
|View full text |Cite
|
Sign up to set email alerts
|

Redox-dependent Matrix Metalloproteinase-1 Expression Is Regulated by JNK through Ets and AP-1 Promoter Motifs

Abstract: present study, we investigate the molecular mechanisms involved in the H 2 O 2 -mediated induction of MMP-1. Mutational analysis of an MMP-1 promoter indicates that both the single nucleotide polymorphism creating an Ets binding site at ؊1607 and a proximal AP-1 site at ؊1602 are required for maximal H 2 O 2 -dependent transcription. The redox-sensitive MMP-1 protein expression requires activation of both ERK1/2 and JNK pathways. Importantly, JNK signaling is largely responsible for the H 2 O 2 sensitivity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 54 publications
7
69
0
1
Order By: Relevance
“…In addition, it has been recently suggested that ROS produced by cytokines and nitric oxide would be a second messenger to stimulate JNK, and some low molecular weight G proteins (such as p21rea, Rac1 and CDC42) might be sensors in JNK activation for ROS [45]. Upregulation of MnSOD as reported in the present study leading to accumulation of H 2 O 2 could also lead to phosphorylation and activation of JNK as reported by other studies [46].…”
Section: Discussionsupporting
confidence: 69%
“…In addition, it has been recently suggested that ROS produced by cytokines and nitric oxide would be a second messenger to stimulate JNK, and some low molecular weight G proteins (such as p21rea, Rac1 and CDC42) might be sensors in JNK activation for ROS [45]. Upregulation of MnSOD as reported in the present study leading to accumulation of H 2 O 2 could also lead to phosphorylation and activation of JNK as reported by other studies [46].…”
Section: Discussionsupporting
confidence: 69%
“…Indeed, adjacent AP1 and Ets motifs in promoters can form so-called Ras-responsive elements that mediate cellular responses to Ras-MAPK signaling (McCarthy et al, 1997;Westwick et al, 1994;Yang et al, 1996). Similar AP1 and Ets motifs have been detected within the promoters of Mmp genes, where they play a major role in regulating expression of these genes (Kapila et al, 2009;Nelson et al, 2006;Watabe et al, 1998). Several Mmp genes demonstrate dramatically increased expression in E18.5 BT skin, and we have previously demonstrated upregulation of many Mmp genes in epidermis of BT mice induced at an adult age (Nagarajan et al, 2009).…”
Section: Ets1 Expression In Differentiating Keratinocytes Induces Expmentioning
confidence: 99%
“…5,7,, an analog of vitamin E has been widely investigated for its role in the inhibition of oxidative stress or damage in cancer cells (Lúcio et al, 2009;Barclay et al, 1995;Forrest et al, 1994). Further, its effect has also been investigated in induction of antioxidative effect through expression of MMP in inflammatory diseases and cancers (Haug et al, 2004;Nelson et al, 2006). It has been reported that MMPs play a vital role in the process of human lung and cervical cancer metastasis (Nelson et al, 2000;Sheu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%